The variance on the shock response of a carbon fibre composite due to the orientation of the weave - Wood, David C.; Appleby-Thomas, Gareth J.; Hameed, Amer; Barnes, Nick R.; Hughes, A.; Hazell, Paul J. (Springer, 2018)
Three different orientations of a tape-wrapped carbon fibre composite with phenolic resin matrix (abbreviated to TWCP) have been investigated under one-dimensional shock loading. This has been achieved via a single-stage gas gun, with manganin gauges as the diagnostic tool. The orientations of TWCP studied in this paper were 25°, 45° and 90°, with respect to the impact face. The shock response of these orientations, for this material, has been obtained (the Hugoniot equation of state). These results have been contrasted with previously reported literature data for the same material at different orientations (0° and 20°). It was found that orientation had minimal effect on the behaviour of this composite under shock. The exception to this was the 90° orientation which exhibited an elastic precursor at particle velocities of less than 0.65 mm µs−1; where the shock velocity was equivalent to the elastic sound speed of the material.